Study of suitability postharvest handling level of potatoes in Kerinci District. Issue 1 (November 2021) - Nofriati, D; Hernita, D; Hendri, J; Salvia, E; Primilestari, S
Abstract: Almost 60% of Jambi Province's potato production comes from Kerinci District. As well as other food crop products, productivity must be balanced with the quality of the produced. Postharvest handling based of Good Handling Practices concept is the key to producing high quality and competitive potatoes and optimizing the results obtained. The data obtained showed that there was a decrease in potato seed yield around 16% during the storage. The loss was contributed by rotten and moisure migration tubers. Very few studies have been conducted to evaluate the appropriateness of postharvest handling of potatoes according to GHP concept in Kerinci District. Therefore, purpose of the study was to determine the level of suitability of postharvest handling of potatoes in Kerinci District. The research method is descriptive exploratory by making hostages systematically, factually and accurately. The data were obtained through observation, interviews and calculating the percentage of postharvest handling suitability based of the GHP concept. The results showed that the level of suitability for postharvest handling of potatoes in Kerinci District was around 69% with the average improvement that had to be done at the cleaning, storehouse handling, sanitation and packing type stages around 31% and digging tube loss reaching 100%. In principle, carrying out potato postharvest activities based of the GHP recommendations is an effort to minimize yield losses. The results of this study are expected to be a solution for improving the quality and competitiveness of potato commodities in Kerinci District, Jambi Province.